Semiotic Analysis and Persuasive Discourse to the Billboard of Legislative Candidates 2019 In Indonesia - Lely Rahmawati; Emzir Emzir; Shafruddin Tajuddin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to scrutinize the utilization both of visual and written language toward the billboard of legislative candidates in the general election 2019. The sources of the data are 2 billboards from 9 parties winning the general election 2019 in Indonesia and the data that has been taken by the researchers are slogans and photos which have been deployed on the billboards. This qualitative research uses the method of descriptive analysis. On billboard 1 (Golkar), the dominance of the persuasive discourse is a wise clause which has been deployed to build a good reputation about legislative candidates. Meanwhile on billboard 2 (PKS), the dominance is the invitation which indicated that the legislative candidates directly invited the people to choose them. Through the visual and written language, the legislative candidates showed their identities strongly. Briefly, these billboards which showed in this research contained the strong persuasive language which combined both of written and visual languages. Keywords: Language, Persuasive, Visual, Parties